PENDIDIKAN NILAI MELALUI UKM FKIP MENGAJAR ULM SEBAGAI DAYA DORONG PENCAPAIAN KARAKTER PRESTASI - Sigit Ruswinarsih; Rahmat Nur; Sofyan Sauri; Aceng Kosasih; Eka Nur Hidayah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Value education implemented in the form of student character education is an effort to instill noble values. Student involvement in organizational activities such as student activities units (UKM) aims to shape the character of achievement. This study aims to reveal the driving force for students to join UKM. In turn, activities in UKM make education valuable for the formation of student character based on the value of achievement. As the research method, a qualitative research approach was chosen through the case study method at UKM FKIP Mengajar Lambung Mangkurat University. The result of the study illustrates that students are encouraged to participate in activities because of the need for achievement, power or leadership, and social relationships or interactions with other people and groups. This drive makes the student’s character stronger and can become their provision as agents of change.